The relationship between coastal weather and foraging behaviour of chinstrap penguins, Pygoscelis antarctica - Lowther, Andrew D; Trathan, Phil; Tarroux, Arnaud; Lydersen, Christian; Kovacs, Kit M (ICES Journal of Marine Science, 2018)
There is increasing interest in using higher-trophic level predators as ecosystem indicators because their performance is presumed to be linked to the overall function of the ecosystem that supports them. In the southwest Atlantic sector of the Southern Ocean, Antarctic krill (Euphausia superba) supports huge predator populations as well as a growing commercial fishery. To utilize information from the ecosystem in an adaptive framework for sustainably managing krill catch levels, performance indices of krill predators have been proposed as a proxy for krill abundance. However, there are several potentially confounding sources of variability that might impact predator performance such as the effects of environmental variability and fishing pressure on krill availability at scales relevant to predators. In this context, our study capitalises on the occurrence of an unexpected El Niño event to characterise how environmental variability can drive changes in predator foraging behaviour. We demonstrate a clear link between coastal downwelling and changes in the at-sea habitat usage of chinstrap penguins (Pygoscelis antarctica) foraging in a local krill fishing area. Penguins tracked from their breeding colonies on Powell Island, Antarctic Peninsula, undertook fewer, longer foraging trips during the downwelling-affected season compared with the season where no such downwelling was detected, suggesting that changes in climate-driven oceanography may have reduced krill availability along the northern shelf of the island. Our study demonstrates that penguin foraging behaviour is modified by scale-dependent processes, which if not accounted for may result in erroneous conclusions being drawn when using penguins as bioindicators of krill abundance.
Keywords: Sørishavet; marinbiologi; meteorologi; ornitologi; pingviner; økologi

Fjerning av reinsdyr på Sør-Georgia: nok et avsluttet kapittel i norsk hvalfangsthistorie - Kilander, Carl Erik (Polarboken, 2014)
Keywords: Sørishavet; zoologi; økologi

Antarctic krill swarm characteristics in the Southeast Atlantic sector of the Southern Ocean - Krafft, Bjørn A.; Skaret, Georg; Knutsen, Tor; Melle, Webjørn; Klevjer, Thor; Søiland, Henrik (Marine ecology. Progress series, 2012)
Knowledge about swarm dynamics and underlying causes is essential to understand the ecology and distribution of Antarctic krill . We collected acoustic data and key environmental data continuously across extensive gradients in the little-studied Southeast Atlantic sector of the Southern Ocean. A total of 4791 krill swarms with swarm descriptors including swarm height and length, packing density, swimming depth and inter-swarm distance were extracted. Through multivariate statistics, swarms were categorized into 4 groups. Group 2 swarms were largest (median length 108 m and thickness 18 m), whereas swarms in both Groups 1 and 4 were on average small, but differed markedly in depth distribution (median: 52 m for Group 1 vs. 133 m for Group 4). There was a strong spatial autocorrelation in the occurrence of swarms, and an autologistic regression model found no prediction of swarm occurrence from environmental variables for any of the Groups 1, 2 or 4. Probability of occurrence of Group 3 swarms, however, increased with increasing depth and temperature. Group 3 was the most distinctive swarm group with an order of magnitude higher packing density (median: 226 ind. m ) than swarms from any of the other groups and about twice the distance to nearest neighbor swarm (median: 493 m). The majority of the krill were present in Group 3 swarms, and the absence of association with hydrographic or topographic concentrating mechanisms strongly suggests that these swarms aggregate through their own locomotion, possibly associated with migration.
Publisher: Inter-Research
Keywords: Bouvetøya; Sørishavet; datainnsamling; ekkolodd; krill; marin biologi; plankton; økologi